Evolution of stakeholder behavior strategies under cap-and-trade of the benchmark method - Dazhi Linghu; Jin Cui; Haicang Yan; Xinli Wu (Humanities & Social Sciences Communications, 2025)
Abstract This study establishes a carbon emission reduction supply chain mechanism for government-enterprise-consumer cooperation based on the cap-and-trade benchmark method that considers consumers’ willingness to pay, government regulation, and enterprise’ profit-driven motives. Then, in this research, a tripartite evolutionary game model of carbon emissions reduction between the government, high-emission enterprises, and low-emission enterprises is developed to examine the incentives for heterogeneous enterprises to reduce emissions in response to government subsidies, emission benchmark, carbon price and consumers’ carbon preferences. The results show that an increase in the government subsidy rate will effectively incentivize heterogeneous enterprises to reduce emissions and that differential subsidy rates should be set for heterogeneous enterprises. Making only emissions benchmark changes does not change the emission reduction decisions of heterogeneous enterprises. An increase in the price of carbon trading is the only factor that can incentivize both high- and low-emission enterprises to reduce emissions and innovate, as well as incentivize strict government regulation. An increase in the degree of consumer preference can effectively incentivize heterogeneous enterprises to reduce emissions.